Penyuluhan Manfaat Dan Dampak Penggunaan Internet Bagi Karang Taruna Di Kelurahan Pancoran Mas Depok - Fauziyah, Fauziyah; Lestari, Dwi; Zulkarnain, Iskandar (LPPM Universitas Bung Karno, 2022)
Nowadays the internet is one of the needs in human life, and offers easy access to information and ease of communication, the benefits provided by the use of the Internet in everyday life are unquestionable. In all fields of the internet, there is a very important role. In the world of society the internet is also very helpful. A lot of human activities and interaction with the help of the internet. There is a term that says that the internet is like a double-edged knife: there is a positive impact and there is also a negative impact that we get. The use of the internet must be wise in choosing and sorting out existing information. The negative effects of using the Internet are currently a concern for many parties and how it affects society, especially its effect on adolescent children.